DESCRIPTION OF STUDENT'S MATHEMATIC COMMUNICATION ABILITY REVIEWING FROM PERCEPTION OF MATHEMATICS - Joko Purwanto; Cahya Setyautami; Gunawan Gunawan; Nuhyal Ulia; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2022)
This study aims to describe the mathematical communication skills of class VII students in terms of students' perceptions of mathematics in class VII statistics material. The data sources of this research were students of class VII C of SMP Negeri 1 Sumbang. Respondents in this study were taken by purposive sampling method. Students are categorized into three categories, namely high, medium, and low perceptions of mathematics. The method used for data collection in this study was a questionnaire on students' perceptions of mathematics, mathematical communication skills tests, and interviews. Based on the results of research that has been done, it can be concluded that students who have a good perception of mathematics are able to meet the three indicators of mathematical communication skills, students who have an ordinary perception of mathematics are quite capable of meeting the three indicators of mathematical communication skills and students who have poor perceptions towards mathematics tend not to be able to meet the indicators of mathematical communication skills